The Effect of ESG Disclosure on Financial Performance and Company Value With an Independent Board of Commissioners As A Moderation in JII Companies - Putri Wahyuni; Rahma Wijayanti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to obtain empirical evidence regarding the effect of Environmental, Social, and Governance (ESG) disclosure on financial performance projected by Return on Assets (ROA) and firm value projected by Tobin’s Q. Furthermore, this study aims to examine the role of Independent Commissioners as a moderating variable in the relationship between ESG disclosure on financial performance and firm value in issuers listed on the Jakarta Islamic Index (JII). This research uses a quantitative approach with secondary data obtained from annual reports and sustainability reports. The population in this study are companies listed on the Jakarta Islamic Index (JII) for the 2022-2024 period. The sampling technique used purposive sampling method. Data analysis was performed using multiple linear regression techniques and Moderated Regression Analysis (MRA) to test the moderation effect with the help of statistical software. The results of this study are expected to contribute academically regarding the importance of ESG disclosure in increasing the value and performance of Sharia companies in Indonesia. The findings of this study are predicted to prove the positive influence of ESG on profitability (ROA) and market response (Tobin’s Q), as well as confirming the effectiveness of Independent Commissioners in strengthening these relationships to mitigate greenwashing risks.